Analisis Pemanfaatan Lidi Kelapa Sawit Dalam Meningkatkan Pendapatan Dan Ketidakseimbangan Ekonomi Masyarakat (Studi Kasus : Berkah Lidi Di Desa Sei Rumbia Kec. Kota Pinang Kab. Labuhanbatu Selatan) - Nasution, Dini Andriani; Lubis, Annisa Zahra; Nasution, Juliana (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
The extent of community oil palm plantations is directly proportional to the amount of waste produced,one of which is the only way to deal with it.But with the blessing of creative industry sticks can make sticks that were once considered waste transformed into a staple of economic value .This study aims to determine how the impact of the use of oil palm sticks to increase the income of the economic welfare of the community in the village kotapinang this study uses qualitative research methods.Data collection is done through in-depth interviews then supported literature studies .The results and Research show that the existence of creative industry blessing sticks a positive impact on the surrounding community . In addition, the keratif berkah lidi industry can open new jobs for the surrounding community so as to increase community productivity and reduce the level of unemployment.